AUTHENTIC MATERIALS IN EXTENSIVE READING CLASS AT STAIN PONOROGO - Kirana, Dhinuk Puspita (Kodifikasia, 2013)
It is widely believed that English Foreign Language (EFL) learners need todevelop their language proficiency by getting so much input. Moreover, studentsneed to be familiarized with the real English usage where real forms ofcommunication and cultural knowledge are crucially exposed. Teaching throughauthentic materials will make the learners feel that they are learning a reallanguage which is used by the real native speakers for real communication.incorporating authentic materials helps students acquire an effectivecommunicative competence in the language focus. The research intended todescribe the implementation of authentic materials in extensive reading class, theproblems arise and the studentsâ responses toward the authentic materials inextensive reading class. The design of the research was Descriptive Qualitativemethod and the research subject was the lecturer of Extensive Reading class and33 students in B class of the fourth semester of STAIN Ponorogo who tookExtensive Reading subject. The instruments used were in the form of observationsheet, interview guideline and questionnaire. The implementation of authenticmaterials in extensive reading class covered some procedures into three mainphases namely (1) Pre-Activity, (2) Main-Activity and (3) Post-Activity. Theactivities in main activity are as follows: (a) Pre-Activity; (b) Whilst-Activity; and(3) The language focus stage. There were problems arose during theimplementation in terms of complicated planning, more time allocation and somedisinterested students. Finally, the students showed significantly positive attitudetoward the implementation of authentic materials in extensive reading class.